Gangrenous cholecystitis: Analysis of imaging findings in histopathologically confirmed cases - Binit Sureka; Archana Rastogi; Amar Mukund; Shalini Thapar; Ajeet Singh Bhadoria; Tushar Kanti Chattopadhyay (Indian Journal of Radiology and Imaging, 2018)
Purpose: To study the imaging findings in gangrenous acute cholecystitis. Materials and Methods: Retrospective analysis of imaging findings in 31 histopathologically confirmed cases of gangrenous cholecystitis was done. The following imaging findings were analyzed: wall thickness, gallbladder distension, intraluminal membranes, mural striation, edema, wall enhancement, gallstones, gas, pericholecystic fluid, stranding, hemorrhage, hyperaemia in adjacent liver, mucosal/wall irregularity, complications. Statistical Analysis: Appropriate statistical tests were used using SPSS.22.0 software. The two proportions were compared using Chi-square or Fisher exact test and two means were compared using student t test. Results: Mean gallbladder wall thickening was 6 ± 1.93 mm. Gallstones, mural edema, mural striation, pericholecystic fluid, intraluminal membranes, gas were seen in 30, 27, 18, 20, 14 and 3 cases respectively. The mean short-axis distension of gallbladder lumen was 4.24 ± 0.91 cm. Gallbladder wall enhancement was studied in only 10 cases. Complete absence of enhancement was seen in 1, focal decreased enhancement in 8 cases. Mucosal/wall irregularity was seen in 28 cases. 74.2% cases had ≥4 cm gallbladder distension. Intraluminal membranes were present in 14 cases with mean short-axis distension of 4.6 cm and absent in 17 (P = 0.041), in 11 cases with mural striation (P = 0.036). Mean wall thickening was 6.69mm in patients with intraluminal membranes and 5.46 mm with absence of membranes (P = .078). Conclusion: Presence of more than one of these findings - gallbladder distension (short axis diameter of ≥4 cm), intraluminal membranes, mural striation, absent or decreased enhancement of gallbladder wall suggest high probability of gangrenous change in acute cholecystitis.